The current state of the humus content of arable chernozems of the true steppes (the example of the Rostov region, Russia) - O. V. Chernova; I. O. Alyabina; O. S. Bezuglova; Yu. A. Litvinov (Юг России: экология, развитие)
Aim. To estimate the humus content and stocks of arable chernozems of two soil-ecological zones (Predcaucasia and Yuzhno-Russkaya) within the Rostov region, as well as the possibility of the optimization of the state of their humus under current conditions.Material and Methods. The following data sources were used: soil and general geographic information accumulated in the Soil-geographic Database of the Russian Federation information system, the Red Book of the Rostov Region Soils database, digitised archived soil survey data of 1977-1995 and agrochemical monitoring data of 2012-2017.Results. The stabilisation of the humus content of the arable chernozems of the Predcaucasian zone in recent decades has been demonstrated and can be explained by a decrease in the dehumification rate under minimal tillage. The average humus content in the soils of the Yuzhno-Russkaya zone decreased by approximately 0.5% during the same period, which may be caused by the high proportion of row-crops cultivated in an erosion-prone area. The current average humus content in arable chernozems is very low, it is close to the critical level, below which crop yield is decreased despite of sufficient mineral fertilizers using.Conclusion. The main causes of soil dehumification in the region are agrogenic humus mineralization due to a constant deficit of compensating amounts of fresh organic matter, deflation of fine soil material from ploughed surfaces and water erosion. The optimisation of land use structure and crop structure, which takes into account the characteristics of these territories, is required to reduce the intensity of these processes under current conditions.